Surgical treatment of carotid artery stent infection: a case report. Issue 2 (February 2021) - Liu, Xiwen; Zhao, Yue; Zhao, Fucheng; Guo, Suli; Sun, Daju
The most effective treatment for graft infection is still debated, and the success rate of current treatments is low. We herein report the results of surgical treatment and follow-up of a case of infection acquired during carotid stenting with the aim of exploring the most effective treatments for graft infection. We retrospectively analyzed a patient who was admitted in September 2019. This patient underwent debridement, autologous saphenous vein replacement of the common carotid to internal carotid artery, external carotid artery suturing, and continuous negative-pressure wound therapy for carotid stent infection. Ten days after carotid artery revascularization, the growth of granulation tissue in the incision was good, and we decided to suture the neck incision. Five days after removing the stitches, grade A healing was noted. Furthermore, the carotid artery and autologous vein grafts were unobstructed as shown by carotid artery computed tomography angiography reexamination. The patient was monitored for 8 months with no new neurological symptoms and good healing of the incision. Effective treatment of vascular graft infection includes debridement and removal of the infected graft, autologous vein graft revascularization, and negative-pressure wound therapy combined with antibiotic therapy.